Stability of PAC (Psy-2A-CrtI) gene and agronomic traits in the F2:3 of IR36/PAC transgenic plants - Hyun Suk Lee; Gihwan Yi; Kyung Min Kim (Journal of Integrative Agriculture, 2015)
This study was carried out to evaluate the expression of yellow endosperm color in the progeny of Psy-2A-CrtI (β-carotene gene, PAC) transgenic plants crossed with IR36. The selected 25 lines of F2 progeny exhibited stable expression of yellow endosperm color and high agronomic characteristics. IR36 and PAC transgenic plant of the grain length, width and ratio showed the same tendency of normal distribution. For progeny selection, colorimeters were as employed to distinguish differing visible colors. Correlation analysis was conducted to investigate the relationship between b* value and the expression of specific genes. b* value was associated with the relative expression of the PAC-Rev and MAR product by real-time PCR and t-test revealed significant difference. Based on this study, correlation between colorimetric values and real-time PCR was effective to detect gene expression. Yellow endosperm progenies represent a new genetic pool that might be useful to increase the genetic diversity of yellow endosperm rice.